MARKETING MIX OF ISLAMIC EDUCATION SERVICES - Setiowati, Lilis; Khairunnisa, Aisyah; Annur, Saipul; Yuniar, Yuniar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Marketing mix is an important concept in marketing strategy involves the integration of various key elements, such as product, price, distribution, and promotion, to meet market needs and achieve business goals. In the context of Islamic education services, the application of the marketing mix concept it is becoming increasingly important to ensure effectiveness in attracting interest and maintaining public trust in educational services Islam. This article reviews the importance of a deep understanding of this issue typical characteristics of Islamic education services and how these factors can be influence effective marketing strategies. Apart from that, this article too discusses appropriate market segmentation, use of internal innovation marketing, and the influence of religious values in formulating strategies responsive and integrated marketing. Through a thorough review to current literature and practice, this article provides insight in depth about the importance of adopting an appropriate marketing mix and innovative in the context of Islamic education services to ensure growth and the sustainability of educational institutions amidst challenges and changes continuously in the world of education and marketing.